Head and neck free flap survival when requiring interposition vein grafting: A multi-instiutional review. (February 2020) - Seim, Nolan B.; Old, Matthew; Petrisor, Daniel; Thomas, William; Naik, Akash; Mowery, Alia J.; Kang, Stephen; Li, Ryan; Wax, Mark K.
Highlights: To further study survival rates of head and neck free flap reconstructions requiring interposition vein grafts. To identify any risk factor predicting free flap demise in this setting. To study if soft tissue vs osteocutaneous free flaps have differing survival rates with interposition vein grafting. Abstract: Objective: Interposition vein grafting in free flap reconstruction is often viewed as a risky procedure, but is necessary in cases of inadequate pedicle length. Materials and methods: Two tertiary care centers retrospectively.reviewed 3008 head and neck free flap reconstructions from 2008 to 2017 91 patients were identified requiring interposition vein grafting during reconstruction. Pre and perioperative characteristics were recorded Univariate and multivariate analyses were conducted with a p value <0.05 indicating statistical significance. Results: Of the 91 patients 75% had undergone reconstruction for cancer, 66% of these cases were in the setting of recurrence or complication, 33% had a previous free flap, and 52% had prior radiation therapy. Surgical site was primarily craniofacial (36%) or oral cavity (26%). The majority of vein grafts were saphenous (64%), average graft length 18 cm (SD 11 cm). Half were used for both artery and vein anastomosis. Flap survival was 85% overall and only prior free flap was predictive of failure on multivariate analysis. No other peri -operative or graft variable assessed in this study were predictive of flap failure. Conclusion: In a multi-institutional study of head and neck free flap reconstructions using interposition vein grafts, we identified an overall 85% success rate with no significant difference between soft tissue and osteocutaneous flaps despite the complicated nature of these cases.